TAXONOMIC REVISION OF CRATOPUS SCHOENHERR (CURCULIONIDAE: ENTIMINAE) FROM INDIA - G. MAHENDIRAN; V. V. RAMAMURTHY (The Bioscan, 2013)
Two species of the genus Cratopus (Curuliondiae: Entiminae) known from India are revised. The generic and species descriptions are updated through addition of measurements and description of elytral vestiture characters. A modified key to the species of Cratopus is provided.